Effect of ratio of ethylene glycol/water and concentration of ammonium fluoride on the synthesis of Cu2o nanostructures By Anodizing - Yeoh, Shi Rou (School of Material Engineering, University Malaysia Perlis, 2016)
Cuprous oxide (Cu2O) nanostructures have been synthesized via anodizing process in ethylene glycol electrolyte with different water content and concentration of NH4F. The effects water content in ethylene glycol electrolyte and concentration of NH4F on the synthesis of Cu2O nanostrucutres were studied. The water contents in the EG electrolyte were varied from 5 vol.% to 25 vol.% with 0.15 M KOH and 0.10 M NH4F meanwhile the concentration of NH4F in the EG electrolyte were increased from 0.05 M to 0.25 M with 0.15 M KOH and 5 vol.% of water. Moreover, the anodizing behavior, microstructure, compositions and optical properties of these Cu2O nanostructures were studied by using FESEM, EDX, XRD, FTIR and PL. FESEM results show that the Cu2O nanostructures with different morphologies due to different water content and concentration of NH4F added in the EG electrolyte. The lattice planes of Cu2O were attributed to (111), (200), (220) and (311). For FTIR, the absorption peaks of Cu2O appeared within 550-840 cm-1. Last but least, the band gap of Cu2O nanoparticles is 2.83 eV and 1.97 eV which obtained from PL characterization